Optimalisasi Peran Dosen Agama Melalui Khutbah Jumat Sebagai Metode Mendidik Masyarakat di Masjid Al-Hidayah Simpang Periuk Lubuklinggau - Sujarwo; Muhamad Akip; Mukhlas (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
The aim of this service activity is to improve the skills of lecturers and the tridharma of higher education in the form of delivering sermons at the Al Hidayah Mosque, Simpang Periuk Lubuklinggau. This community service is carried out every once in a while, where sermons are given by the management of the Al Hidayah Mosque with an attached schedule for one year. The problems faced by the lack of preachers at the Al Hidayah Mosque and the lack of religious knowledge among the congregation at the Al Hidayah Mosque. By optimizing the role of religious lecturers, it is hoped that academic institutions and the wider community will be able to provide improvements in worship, religious knowledge and be able to carry out Friday prayers well and produce articles in the form of national scientific journals.